In India's Reang Tribe, a Model for Improved Development of New Followers - Dr. Rashpal Singh, Dr. Rajni Bala (International Journal of Advanced Science and Technology, 2020)
Religion has been an important aspect in the course of development regarding culture, heritage and social solidarity of any community. The religion of the Reang (Bru) community is the resultant of traditions and beliefs that have come down to them from antiquity.The Reang (Bru) are one of the tribes residing in the states of Tripura, Mizoram, and Assam. They belonged to the Mongoloid groups and speaks the Tibeto-Burman language ‘Kau Bru’. They have a religious practices and usages of their own for ages. Major rituals of the Reang (Bru) community performed by the priest include the entire rituals starting from birth to death.The influence of Christian and Hindu religions has been a dominating force in eliminating most of these religious belief and practices. But, their influence among the Reang (Bru) community has been revitalization for the search of a new ideology, which aims at securing an efflorescence of a new identity.This paper is an attempt to examine the indigenous tribal religion with respect to its tradition and the transformation from the indigenous point of view.